Blue light-directed destabilization of the pea Lhcb1*4 transcript depends on sequences within the 5' untranslated region. - Anderson, M B (1999)
Pea seedlings grown in continuous red light accumulate significant levels of Lhcb1 RNA. When treated with a single pulse of blue light with a total fluence >10(4) micromol m(-2), the rate of Lhcb1 transcription is increased, whereas the level of Lhcb1 RNA is unchanged from that in control seedlings. This RNA destabilization response occurs in developing leaves but not in the apical bud. The data presented here indicate that the same response occurs in the cotyledons of etiolated Arabidopsis seedlings. The blue light-induced destabilization response persists in long hypocotyl hy4 and phytochrome phyA, phyB, and hy1 mutants as well as in far-red light-grown seedlings, indicating that neither CRY1 (encoded by the hy4 locus) nor phytochrome is the sole photoreceptor. Studies with transgenic plants indicate that the destabilization element in the pea Lhcb1*4 transcript resides completely in the 5' untranslated region.